PAIKEM through Live Music and Gathering to Improve Student Achievement in Doremi Home Music Course Ponorogo - Evi Muafiah; Vivi V. W. Damayanti; Puji Ariyanti (AL-ISHLAH: Jurnal Pendidikan, 2021)
Learning using the active, innovative, creative, effective, and fun participation methods is a learning process by creating an atmosphere in such a way that students actively participate in learning process. The methods facilitated students in building their process of behavior change towards a better direction while accommodating students' thoughts, ideas, creativity to achieve goals or at least achieve basic competencies set by the teacher by creating a pleasant of learning atmosphere. This method also applies to music education. Music education is a determining factor in shaping a child's personality. Doremi Home Music Course is a course and training institution engaged in music training. This research and development showed that using the learning model with life music and gathering can improve student achievement in Doremi Home Music Course. The design of the learning model for live music and gathering with the application of the active, innovative, creative, effective, and fun participation method has a high degree of permanence.